Pengaruh Tata Kelola Perusahaan dan Carbon Emission Disclosure terhadap Kualitas Pelaporan Keberlanjutan (Studi pada Perusahaan Sektor Maritim dan Logistik yang Terdaftar di Bursa Efek Indonesia Periode 2021–2024) - Zeynep Aslan; Meutia Riany (Worksheet : Jurnal Akuntansi, 2026)
This study aims to empirically examine and analyze the partial and simultaneous effects of corporate governance and carbon emission disclosure on the quality of sustainability reporting. This study uses a quantitative approach with a causal research design. The population in this study consists of maritime and logistics companies listed on the Indonesia Stock Exchange during the 2021–2024 period. Based on the sample selection criteria, 17 companies were obtained as research samples with a total of 68 observations. Data analysis used panel data regression, where the most consistent and appropriate model used was the Common Effect Model (CEM). The results show that corporate governance partially has no significant effect on the quality of sustainability reporting. On the contrary, carbon emission disclosure is convincingly proven to have a positive and significant effect on improving the quality of sustainability reporting. Furthermore, simultaneous testing proves that the integration between corporate governance structure and transparency of carbon emission disclosure is simultaneously able to provide a significant effect on the quality of sustainability reporting. The synergy of these two elements creates a highly effective dual control ecosystem in validating the push of Legitimacy Theory , even though current internal oversight mechanisms tend to still be oriented toward administrative compliance and financial targets alone.